Pembuatan Pupuk Organik Cair Berbahan Dasar Limbah Organik Pasar MMTC Medan - Saronom Silaban; Murniaty Simorangkir; Juniar Hutahaean; Choms Gary Ganda Tua Sibarani; Marudut Sinaga; Bajoka Nainggolan; Martua Haojahan Saragih; Kristin Wulan Liberti Vivanis Gulo; Litani Fivetrin Siregar; Fuaddinda Putri Salsabila (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
This community partnership program (PKM) activity aims to train and assist farmer group partners "Kelomtawar" to make liquid organic fertilizer (POC) based on organic waste at the MMTC Medan market. Organic waste in the form of vegetables and fruits obtained from the MMTC Medan market is used as the main raw material for making POC. In this activity, technology transfer is carried out in the form of appropriate technology for processing POC, namely composter. The method of implementing the activities carried out is the P3 approach, namely planning, training, and mentoring. The result of PKM activities is the increased knowledge of partners in making POCs based on organic waste. The use of organic waste-based POCs can reduce agricultural production costs for partner groups.